Pengaruh Citra Merek, Kualitas Produk, dan Harga Terhadap Keputusan Pembelian produk Cok Ko Tengok (CKT) Pada Masyarakat Kota Pematang Siantar - Simanjuntak, Clinderton Alfrado; Purnomo, Hadi (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The purpose of this study determines variables of brand image, product quality and price have a partial and simultaneous influence on the purchase decision of Cok Ko Tengok products in the people of Pematang Siantar city.This study used a quantitative approach and the sampling used a non-probability sampling method with 96 sample, analyzed using regression analysis and the analysis tool, SPSS. Based on the test results on data that has been collected through questionnaires distributed. The results of the first hypothesis were obtained that the brand image variable had a significant and simultaneous effect on purchasing decisions, product quality was not significant on purchasing decisions but had a simultaneous effect, price had a significant and simultaneous effect.